Report of the Technical Committee to Study the Requirement of Major Electrical Equipment 1965 - Planning Commission (Planning Commission Government of India, 1965)
The Technical Committee Report on Major Electrical Equipment (1965), prepared under the aegis of the Planning Commission of India, assesses the requirements for electrical equipment needed to support the power generation and transmission targets of the Fourth and Fifth Five-Year Plans. The report projects a substantial expansion in installed power capacity, driven by anticipated economic growth and rising energy demand, with a balanced emphasis on hydroelectric, thermal, and nuclear power generation. It evaluates the readiness of domestic manufacturing capabilities for turbines, generators, transformers, and electric motors, identifying areas where capacity expansion and technological upgrading are necessary. Particular attention is given to constraints in the supply of critical raw materials such as copper and silicon steel, highlighting the need to strengthen indigenous production to reduce import dependence. The report concludes with policy recommendations focused on capacity planning, public–private collaboration, technology transfer, and continuous monitoring to ensure a reliable and self-sufficient electrical equipment sector supporting India’s long-term economic development.
Government of India, Planning Commission
Keywords: Major Electrical Equipment; Power Generation Capacity; Fourth Five-Year Plan; Fifth Five-Year Plan; Hydroelectric Power; Thermal Power; Nuclear Power; Turbines and Generators; Transformers Manufacturing; Electric Motors; Indigenous Production; Power Sector Planning